Calculus Calculus Scores and Sleep Quality: A Study of UMN Informatics 2022 - Wibawa, Bonifacius Martin; Revian, Revan; Channiko, William Lo; Halim, Fransiscus Ati (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2025)
This study explores the interplay between academic performance and sleep quality among UMN Informatics students from the 2022 class. Examining calculus scores and Pittsburgh Sleep Quality Index (PSQI) data, the analysis reveals a diverse range of performance in calculus, with a notable concentration of students reporting good sleep quality. Covariance and correlation matrices suggest an inverse relationship between PSQI scores and exam performance, indicating that better sleep quality may be associated with higher exam scores. Shape measure analysis further emphasizes the prevalence of good sleep quality among students. However, residual tests unveil challenges such as heteroscedasticity and autocorrelation, cautioning against overinterpretation of the regression model. The GLS model highlights a significant negative relationship between PSQI scores and exam performance, providing valuable insights into the potential impact of sleep quality on academic outcomes. This study contributes to understanding the complex dynamics between sleep quality and academic achievement, acknowledging the need for nuanced interpretation and consideration of underlying statistical assumptions.